El culto a Júpiter en el Conventus Bracaraugustanus. Los dedicantes y su condición social - García Martínez, Sonia María; Rabanal Alonso, Manuel Abilio (Estudios humanísticos. Geografía, historia y arte, 2001)
During the roman period the cult of luppiter, the most important divinity of the roman pantheon, was very significative in the Conventus Bracaraugustanus, in the Northwest of Spain. In this article, we are going to analyse the repercusion of its cult by people who lived in this part of Hispania.